1983
DOI: 10.1002/app.1983.070281110
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of branched low‐density polyethylene

Abstract: SynopsisThe shear flow properties of six commercially available long-chain branching low-density polyethylene resins were determined, using a cone-and-plate rheometer at low shear rates and a capillary rheometer at high shear rates. Also determined were the elongational viscosities of the resins, using an apparatus developed by Ide and White. Interpretation of the rheological measurements is given with the aid of the molecular parameters, namely, molecular weight and molecular weight distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…In addition, low molecular weight polymer added into the incompatible blend as a compatibilizer causes the viscosities of blend to be decreased because the polymer roles as a plasticizer. Han et al 29,30 also reported a high melt viscosity of compatibilized blends. In this study, however, the viscosities of ternary blends gradually decrease with increase in the compatibilzer content.…”
Section: Rheological Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, low molecular weight polymer added into the incompatible blend as a compatibilizer causes the viscosities of blend to be decreased because the polymer roles as a plasticizer. Han et al 29,30 also reported a high melt viscosity of compatibilized blends. In this study, however, the viscosities of ternary blends gradually decrease with increase in the compatibilzer content.…”
Section: Rheological Propertiesmentioning
confidence: 92%
“…[30][31][32] However, these structures are deformed by elongational shear flow, composition, viscosity ratio, the degree of orientation, and so on. Figure 9 and Figure 10 show the tensile fractured surfaces of ternary Ultem/Vectra B/EI10 blend fibers and Ultem/Vectra B/BI10 blend fibers at the draw ratio of 4, respectively.…”
Section: Morphologymentioning
confidence: 99%
“…The experimental techniques employed are the same as those described in Paper I of this series. 7 The tubular film blowing experiment was conducted, using the apparatus described in Paper I of this ~e r i e s .~ The details of the experimental procedure employed are also described in the same paper.…”
Section: Methodsmentioning
confidence: 99%
“…(10). A comparison of the calculated + p2x + p3x2)e-B4xl (12) and measured gauges for LLDPE is given in Figure FIGURE 5 LLDPE gauge profile comparison.…”
Section: Deformational History Of Lldpeildpe Blendsmentioning
confidence: 99%